The overall and domain-specific quality of life of Chinese community-dwelling older adults: the role of intrinsic capacity and disease burden - Hu, Xiuhua; Ruan, Jian; Zhang, Weibin; Chen, Jie; Bao, Zhijun; Ruan, Qingwei; Yu, Zhuowei (Frontiers in Psychology, 2023)
Objective This study aimed to investigate the impact of the different domains of intrinsic capacity (IC) and chronic disease burden on health-related quality of life (HRQoL) and domain-specific HRQoL in Chinese community-dwelling older adults. Design A cross-sectional observational study of a community-based cohort. Participants We evaluated Chinese older adults (n = 429, mean age, 72.91 ± 7.014 years; female proportion, 57.30%). Measurements IC contains five domains, namely locomotion, vitality, cognition, psychological, and sensory capacity. Locomotion dysfunction was defined as grip and/or gait decline. Vitality decline was defined if two of the following three parameters were present: fatigue, physical inactivity, and weight loss or overweight. Cognition was classified into normal cognition, pre-mild cognitive impairment (pre-MCI), and MCI according to the normative z-scores of the neuropsychological test battery. Psychological dysfunction was diagnosed based on depressive symptoms. Sensory dysfunction was defined as hearing and/or vision impairment. HRQoL was assessed using the AQoL-8D scale, which comprised physical (including independent living, senses, and pain) and psychosocial (including mental health, happiness, self-worth, coping, and relationships) dimensions. Low HRQoL (HRQoL score or subscores in the highest quintile) was used as a dependent variable in logistic regression analyses adjusted for demographic, health-related, and psychological confounders. Results Sensory impairment was an independent determinant of senses, and locomotion impairment was significantly associated with overall HRQoL, independent living, and pain in the physical dimension of HRQoL. Cognition was an independent determinant of the senses. Vitality was independently associated with overall HRQoL, senses, and pain in the physical dimension and mental health and relationships in the psychological dimension of HRQoL. The psychological domain of IC was independently associated with overall and domain-specific HRQoL apart from senses after adjustment for all confounders. The number of multimorbidities mainly had a significant impact on independent living after adjustment for all confounders. Conclusion IC domains and chronic disease burden had heterogeneous influences on overall and domain-specific HRQoL. The impairment of sensory and locomotion domains had a synergistic impact on the overall and physical dimensions of HRQoL. The vitality and psychological domains of IC had more profound effects on HRQoL. Older people with high morbidity might have a higher risk of poor independent living.